2001
DOI: 10.4049/jimmunol.167.11.6615
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin Induces Activation and Inflammatory Mediator Release from Human Eosinophils Through Protease-Activated Receptor-2

Abstract: Protease-activated receptors (PARs) are a unique class of G protein-coupled receptors, which are activated by proteolytic cleavage of the amino terminus of the receptor itself. PARs are most likely involved in various biological responses, such as hemostasis and regulation of muscle tone; however, the roles of PARs in the functions of inflammatory and immune cells are poorly understood. Because eosinophils are most likely involved in allergic inflammation and are exposed to a variety of proteases derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
4
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 41 publications
9
128
4
1
Order By: Relevance
“…Fibroblasts have been shown to express PAR-2s that mediate tryptase-induced fibroblast proliferation (54), and we presently found that tryptase causes their IL-8 production. Recently, PAR-2 was found to be expressed by peripheral blood eosinophils obtained from normal healthy and mildly asthmatic patients (14). In our study, PAR-2 was also shown to be present on the plasma membrane of eosinophils isolated from the peripheral blood of atopic dermatitis and rhinitis patients.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Fibroblasts have been shown to express PAR-2s that mediate tryptase-induced fibroblast proliferation (54), and we presently found that tryptase causes their IL-8 production. Recently, PAR-2 was found to be expressed by peripheral blood eosinophils obtained from normal healthy and mildly asthmatic patients (14). In our study, PAR-2 was also shown to be present on the plasma membrane of eosinophils isolated from the peripheral blood of atopic dermatitis and rhinitis patients.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, PAR-2 was found to be expressed by peripheral blood eosinophils obtained from normal healthy and mild asthmatic patients (14). In our study, flow cytometric analyses of human peripheral blood eosinophils incubated with anti-PAR-2 Abs showed a strong staining for this receptor (Fig.…”
Section: Par-2 Mediates Tryptase-induced Cytokine Release From the Eomentioning
confidence: 71%
See 2 more Smart Citations
“…It was recently reported that stimulation of PAR-2 with an agonist peptide activates human keratinocytes (42), eosinophils (50), and respiratory epithelial cells (51) to induce inflammatory mediators, and up-regulates keratinocyte phagocytosis (52). PR3 is a major target Ag of antineutrophil cytoplasmic Abs (15, 16) and degrades extracellular matrix proteins (13).…”
Section: Discussionmentioning
confidence: 99%